High plasma levels of soluble LOX-1 portends poor survival in acute coronary syndromes beyond GRACE 2.0: a multicentre prospective cohort study. (14th October 2021) - Kraler, S; Obeid, S; Liberale, L; Von Eckardstein, A; Wenzl, F A; Paneni, F; Matter, C; Muller, O; Raeber, L; Mach, F; Akhmedov, A; Luescher, T F
Abstract: Background: While inflammatory states and dyslipidemias confer a dismal prognosis following myocardial ischaemia, the role of the lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) which sits at the confluence of these conditions remains elusive. Given soluble LOX-1' (sLOX-1) pivotal role in inflammatory processes underlying atherosclerotic plaque progression, we sought to study its prognostic utility on the risk of adverse events in acute coronary syndromes (ACS). Purpose: Hence, we aimed to investigate whether sLOX-1 is an independent predictor of all-cause death at one year beyond traditional and emerging risk factors for poor survival following ACS. Methods: 2678 ACS patients were recruited in the prospective, multicentre SPUM-ACS trial, of which 2525 completed follow-up at one year. Major adverse cardiovascular events, including death from any cause, were adjudicated by an independent clinical endpoint committee. By employing high-sensitive enzyme-linked immunosorbent assay, sLOX-1 was assessed in the plasma at the time of presentation in ACS and age-matched chronic coronary syndrome (CCS) patients. Kaplan-Meier survival analysis and Cox proportional hazard regression models, adjusted for baseline variables and the GRACE 2.0 score, were used to study the predictive utility of sLOX-1. Results: At the time of presentation, ACS patients, specifically those with ST-segment elevation ACS, had significantly elevated sLOX-1 levels as compared to patients with CCS (median, 35.40 vs. 2.00 pg/ml, P<0.0001). Patients in the upper sLOX-1 tertile were at heightened risk for both death from any cause (crude HR 1.785, 95% CI 1.083–2.941, P<0.05; adjusted HR 2.035, 95% CI 1.176–3.519, P<0.05) and CV death (crude HR 2.447, 95% CI 1.285–4.663, P<0.01; adjusted HR 2.383, 95% CI 1.206–4.710, P<0.05) compared to those in the first tertile. Importantly, sLOX-1 remained an independent predictor of all-cause death after adjustment for known risk factors of adverse outcome and the GRACE 2.0 score (adjusted + GRACE 2.0 HR 1.896, 95% CI 1.034–3.476, P<0.05). Conclusions: Plasma sLOX-1 is elevated in ACS patients and predicts poor survival independent of both traditional and emerging risk factors and provides prognostic information beyond GRACE 2.0. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Swiss National Science FoundationFoundation for Cardiovascular Research - Zurich Heart House